Improving adeno-associated viral (AAV) vector-mediated transgene expression in retinal ganglion cells: comparison of five promoters - Nieuwenhuis, Bart; Laperrousaz, Elise; Tribble, James R; Verhaagen, Joost; Fawcett, James W; Martin, Keith R; Williams, Pete A; Osborne, Andrew (Gene therapy, 2023)
Recombinant adeno-associated viral vectors (AAVs) are an effective system for gene transfer. AAV serotype 2 (AAV2) is commonly used to deliver transgenes to retinal ganglion cells (RGCs) via intravitreal injection. The AAV serotype however is not the only factor contributing to the effectiveness of gene therapies. Promoters influence the strength and cell-selectivity of transgene expression. This study compares five promoters designed to maximise AAV2 cargo space for gene delivery: chicken β-actin (CBA), cytomegalovirus (CMV), short CMV early enhancer/chicken β-actin/short β-globulin intron (sCAG), mouse phosphoglycerate kinase (PGK), and human synapsin (SYN). The promoters driving enhanced green fluorescent protein (eGFP) were examined in adult C57BL/6J mice eyes and tissues of the visual system. eGFP expression was strongest in the retina, optic nerves and brain when driven by the sCAG and SYN promoters. CBA, CMV, and PGK had moderate expression by comparison. The SYN promoter had almost exclusive transgene expression in RGCs. The PGK promoter had predominant expression in both RGCs and AII amacrine cells. The ubiquitous CBA, CMV, and sCAG promoters expressed eGFP in a variety of cell types across multiple retinal layers including Müller glia and astrocytes. We also found that these promoters could transduce human retina ex vivo, although expression was predominantly in glial cells due to low RGC viability. Taken together, this promoter comparison study contributes to optimising AAV-mediated transduction in the retina, and could be valuable for research in ocular disorders, particularly those with large or complex genetic cargos.
Keywords: Retinal Ganglion Cells; Humans; genetické vektory; zelené fluorescenční proteiny; Cytomegalovirus Infections; aktiny; Transduction, Genetic; retinální gangliové buňky; Transgenes; Green Fluorescent Proteins; cytomegalovirové infekce; lidé; zvířata; transgeny; myši; transdukce genetická; myši inbrední C57BL; Mice; Mice, Inbred C57BL; Actins; Genetic Vectors; Parvovirinae; Animals; Dependovirus